2022
DOI: 10.3390/chemengineering6030037
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation and Computational Fluid Dynamic Simulation of Hydrodynamics of Liquid–Solid Fluidized Beds

Abstract: The present study provides and examines an experimental and CFD simulation to predict and accurately quantify the individual phase holdup. The experimental findings demonstrated that the increase of solid beads has a significant influence on the (Umf), as comparatively small glass beads particles require a low (Umf) value, which tends to increase as the diameter of the beads increases. Besides that, the expansion ratio is proportional to the velocity of the liquid. Even though, the relationship becomes inverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…However, for velocities higher than terminal velocity (2 79u t , 4 11u t , and 5 42u t ), considerable fluidization is achieved due to drag, as shown in Figures 9-11, respectively. In a similar study, Abdulrahman et al [43] demonstrated the influence of diameter (0.003 m, 0.004 m, and 0.006 m with a density of 2500 kg/m 3 ) of glass spheres and fluid velocity on fluidization velocity in a liquid-solid fluidized bed system; from results, authors informed that the expansion ratio is proportional to the liquid velocity and inversely proportional to the diameter of the beads.…”
Section: Particle'smentioning
confidence: 89%
“…However, for velocities higher than terminal velocity (2 79u t , 4 11u t , and 5 42u t ), considerable fluidization is achieved due to drag, as shown in Figures 9-11, respectively. In a similar study, Abdulrahman et al [43] demonstrated the influence of diameter (0.003 m, 0.004 m, and 0.006 m with a density of 2500 kg/m 3 ) of glass spheres and fluid velocity on fluidization velocity in a liquid-solid fluidized bed system; from results, authors informed that the expansion ratio is proportional to the liquid velocity and inversely proportional to the diameter of the beads.…”
Section: Particle'smentioning
confidence: 89%
“…Particle size has significant effect on the hydraulic resistance of a fluidized bed. With the particle size increase, the hydraulic resistance of the layer increases [11]. Neglecting pressure losses due to friction, the authors of [11] propose an equation for determining the hydraulic resistance of a fluidized bed as following ( )…”
Section: Problem Statementmentioning
confidence: 99%
“…Abdulrahman et al, [14] adopted the Eulerian-Eulerian granular multiphase flow technique to study the performance of liquidsolid fluidized beds. The study quantified the characteristics of both the solid and liquid holdups.…”
Section: Shukla Et Almentioning
confidence: 99%